2013
DOI: 10.1002/jgra.50234
|View full text |Cite
|
Sign up to set email alerts
|

Current structure and nonideal behavior at magnetic null points in the turbulent magnetosheath

Abstract: [1] The Poincaré index indicates that the Cluster spacecraft tetrahedron entraps a number of 3-D magnetic nulls during an encounter with the turbulent magnetosheath. Previous researchers have found evidence for reconnection at one of the many filamentary current layers observed by Cluster in this region. We find that many of the entrained nulls are also associated with strong currents. We dissect the current structure of a pair of spiral nulls that may be topologically connected. At both nulls, we find a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 83 publications
4
52
0
Order By: Relevance
“…Helical field lines of the fans connect the nulls with the external magnetic field. Such topology is very similar to the one deduced from the Cluster observations of a null pair in the Earth's magnetosheath by Wendel & Adrian (2013). Another null pair, observed by Deng et al (2009), has shown quite alarge angle between the spines of the two nulls, as well asa fan-fan separator line.…”
Section: Results: "Multiple Nulls"supporting
confidence: 83%
See 1 more Smart Citation
“…Helical field lines of the fans connect the nulls with the external magnetic field. Such topology is very similar to the one deduced from the Cluster observations of a null pair in the Earth's magnetosheath by Wendel & Adrian (2013). Another null pair, observed by Deng et al (2009), has shown quite alarge angle between the spines of the two nulls, as well asa fan-fan separator line.…”
Section: Results: "Multiple Nulls"supporting
confidence: 83%
“…Isolated magnetic nulls have been studied by means of MHD ) and kinetic particle-in-cell (PIC; Baumann & Nordlund 2012) simulations. Observations, however, have suggested that nulls often concentrate in clusters (Deng et al 2009;Wendel & Adrian 2013). Several 3D MHD simulations addressed multiple null points (Galsgaard & Nordlund 1997;Wyper & Pontin 2014a, 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…2.7.4). Wendel and Adrian (2013) derived the topological degree, or Poincaré index, and discovered magnetic nulls associated with many of the current filaments. The Poincaré index is a measure of the number of roots, 'or magnetic nulls' in a region (Greene 1992).…”
Section: Plasma Phenomena As Measured In Three Dimensionsmentioning
confidence: 99%
“…The determinant and eigenvalues of ∇B studied by Wendel and Adrian (2013) revealed that the null pair consisted of spiral A s and B s nulls. From the eigenvalues of ∇B one can determine the nature of a spine and fan of a null.…”
Section: Plasma Phenomena As Measured In Three Dimensionsmentioning
confidence: 99%
“…To model an encounter with a magnetic null by MMS, we used four-point Cluster data to test techniques for detecting these three-dimensional structures in the dayside magnetosheath (Wendel and Adrian 2013). Nulls are associated with the filamentary substructure of current sheets where reconnection is occurring.…”
Section: Locating Magnetic Nulls In the Magnetosheathmentioning
confidence: 99%